Perceived Value Mediates Product Quality and Price Effects on Purchases at Pandang Kopi, Gianyar, Bali - I Nyoman Hendra Laksmana; Luh Kemala Putri Widhiari; Eldian Rinaldi; Laily Fauziah (Universitas Muhammadiyah Malang, 2026)
The rapid growth of the Indonesian coffee industry has intensified competition among local coffee shop MSMEs, particularly in tourism destinations such as Gianyar, Bali. In this context, understanding how consumers evaluate product quality and price through perceived value is essential for sustaining competitiveness. This study investigates the direct effects of product quality and price on purchasing decisions and examines the mediating role of perceived value among consumers of Pandang Kopi, a local MSME coffee shop. A quantitative approach was employed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). Data were collected from 106 consumers through accidental sampling and analyzed using SmartPLS 4.1.1.2. The results show that product quality (β = 0,159; p < 0,05) and price (β = 0,161; p < 0,05) have positive and significant direct effects on purchasing decisions. Perceived value demonstrates the strongest influence on purchasing decisions (β = 0,683; p < 0,001), explaining a substantial proportion of variance (R² = 0,79). Product quality (β = 0,309; p < 0,001) and price (β = 0,590; p < 0,001) also significantly enhance perceived value. Mediation analysis reveals that perceived value significantly mediates the relationship between product quality and purchasing decisions (β = 0,211; p < 0,001) as well as between price and purchasing decisions (β = 0,403; p < 0,001). Notably, the indirect effect of price through perceived value is stronger than its direct effect, indicating that consumers emphasize overall value rather than price alone. Theoretically, this study contributes to value-based consumer decision models by empirically validating perceived value as a central psychological mechanism in MSME coffee shops located in tourism regions. Practically, the findings suggest that local coffee shop MSMEs should prioritize sensory product quality, fair pricing, and holistic consumption experiences to strengthen perceived value and encourage purchasing decisions.